Application of Coal-Powder Borehole-Sealing Material in Borehole-Sealing Engineering. Issue 2 (13th April 2019) - Li, Hui; Guo, Shaoshuai; Chen, Haidong
Abstract : Coal-powder borehole-sealing technology is a new kind of sealing technology, which has been widely promoted in recent years. It is the technology of mixing pulverized coal and additives in a certain ratio to create a borehole sealing material and then sealing the borehole by pressure grouting. In order to make scientific analysis to the material of the coal-powder borehole-sealing technology and verify its actual sealing performance, this paper made studies using laboratory experiments and field tests. The research results are shown as follows: 1. The borehole sealing material has good micro expansion properties. With the increase of additive proportion, the expansion and strength of the sealing material increases. In addition, the contraction expansibility is also affected by the water-material ratio of the slurry, the smaller the water-material ratio is, the greater the degree of deformation becomes; 2. Considering the powder coal borehole-sealing material's expansion properties, strength characteristics and application cost, determined the optimum composition ratio of powder coal borehole-sealing material: the volume of powder-coal accounted for 70%, and the additive volume accounted for 30%, at this condition, the expansion rate and maximum compressive strength of the sealing material are 6‰ and 7.30 MPa; 3. The gas concentration extracting out of the borehole sealed from using the coal powder sealant is slightly higher than the borehole sealed from using expansive cement (72.50% and 69.65%, respectively).